A SnRK1-ZmRFWD3-Opaque2 Signaling Axis Regulates Diurnal Nitrogen Accumulation in Maize Seeds. Issue 9 (22nd July 2020) - Li, Chaobin; Qi, Weiwei; Liang, Zheng; Yang, Xi; Ma, Zeyang; Song, Rentao
Abstract : Nitrogen assimilation in developing maize seeds is regulated by the SnRK1- Zm RFWD3-O2 signaling axis, which is responsive to diurnal sucrose concentrations. Abstract: Zeins are the predominant storage proteins in maize ( Zea mays ) seeds, while Opaque2 (O2) is a master transcription factor for zein-encoding genes. How the activity of O2 is regulated and responds to external signals is yet largely unknown. Here, we show that the E3 ubiquitin ligase Zm RFWD3 interacts with O2 and positively regulates its activity by enhancing its nuclear localization. Ubiquitination of O2 enhances its interaction with maize importin1, the α-subunit of Importin-1 in maize, thus enhancing its nuclear localization ability. We further show that Zm RFWD3 can be phosphorylated by a Suc-responsive protein kinase, Zm SnRK1, which leads to its degradation. We demonstrated that the activity of O2 responds to Suc levels through the Zm SnRK1- Zm RFWD3-O2 signaling axis. Intriguingly, we found that Suc levels, as well as Zm RFWD3 levels and the cytonuclear distribution of O2, exhibit diurnal patterns in developing endosperm, leading to the diurnal transcription of O2-regulated zein genes. Loss of function in Zm RFWD3 disrupts the diurnal patterns of O2 cytonuclear distribution and zein biosynthesis, and consequently changes the C/N ratio in mature seeds. We therefore identify a SnRK1- Zm RFWD3-O2 signaling axis that transduces source-to-sink signals and coordinates C and N assimilation in developing maize seeds.